2021
DOI: 10.1038/s42004-021-00590-3
|View full text |Cite
|
Sign up to set email alerts
|

The interactive role of methane beyond a reactant in crude oil upgrading

Abstract: Crude oil upgrading under methane has been reported to be an economically and environmentally promising process, while the advantageous effect of methane beyond a reactant is not fully explained. In this work, the catalytic performances, physicochemical properties and regenerability of used catalysts after crude oil upgrading under methane and nitrogen are investigated by n-butylbenzene model compound studies, catalyst characterizations and density functional theory calculations. Comparing to nitrogen, methane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Catalysts with weak acidity tend to dissociate hydrogen protons, a trait favorable for dehydrogenation reactions, which leads to the creation of carbon cations serving as precursors for coke formation. 37…”
Section: Resultsmentioning
confidence: 99%
“…Catalysts with weak acidity tend to dissociate hydrogen protons, a trait favorable for dehydrogenation reactions, which leads to the creation of carbon cations serving as precursors for coke formation. 37…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been observed that methane adsorption is preferential in the internal pores of porous structures such as ZSM-5. 28 The enhancement of mesoporosity can be achieved by post treatment with NaOH, but this can result in desilication and alteration of the acid sites which is not desirable for this reaction, where a pre-determined Brønsted acidity is crucial for methane activation and aromatization. Furthermore, techniques such as this can be time-consuming and not cost effective at the commercial scale.…”
Section: Resultsmentioning
confidence: 99%
“…Investigating the potential of CH 4 as a cost-effective alternative plasma gas could lead to significant advancements in the field of heavy oil upgrading, providing a more sustainable and economically viable approach to this critical industrial process as it can remove the H 2 production step either from endothermic CH 4 reforming or water electrolysis. [4] We, therefore, conceive the use of CH 4 for catalytic upgrading heavy oils with in-liquid plasma in this scenario.…”
Section: Concept Of Using Ch 4 As Plasma Gas To Facility Catalytic Li...mentioning
confidence: 99%
“…[3] Heavy oil's high viscosity poses challenges throughout the extraction, transportation, and refining process, owing to its complex composition containing high molecular weight hydrocarbons, sulfur, nitrogen, oxygen, and metals. [4] The thermal upgrading of heavy oil typically follows two main pathways: carbon rejection and hydrogen addition. [5] Carbon rejection techniques involve extracting light products through thermal cracking methods like delayed coking and viscosity breaking.…”
Section: Introductionmentioning
confidence: 99%